2014
DOI: 10.1111/fwb.12357
|View full text |Cite
|
Sign up to set email alerts
|

Parasite‐induced alterations of host behaviour in a riverine fish: the effects of glochidia on host dispersal

Abstract: Summary Parasitic species can affect host behaviour in various ways. Freshwater mussels of the superfamily Unionoidea have a glochidia larva that is parasitic on fish. Our aim was to evaluate whether fish exposed to glochidia have distinct behaviour that could affect the upstream dispersal of the parasite. Many freshwater mussels are highly endangered, and understanding the relationships with their hosts is important for their conservation. However, research on the behavioural effects of parasitism on fish h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 63 publications
2
41
0
Order By: Relevance
“…If fish hosts do not move far, most mussel propagules will be deposited within the mussel bed leading to localized, positive feedbacks between mussel density, fish hosts, and mussel recruitment. Infestation of European chub (Squalius cephalus) with duck mussel (Anodonta anatina) glochidia resulted in a reduction of the host's activity and movement, restricting mussel dispersal (Horký et al, 2014). Similar to our study, Terui et al (2014) found an overall upstream bias in movements of Masu Salmon (Oncorhynchus masou masou), the host of the Japanese freshwater pearl mussel (Margaritifera laevis), recapturing *70% of hosts near original capture locations.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…If fish hosts do not move far, most mussel propagules will be deposited within the mussel bed leading to localized, positive feedbacks between mussel density, fish hosts, and mussel recruitment. Infestation of European chub (Squalius cephalus) with duck mussel (Anodonta anatina) glochidia resulted in a reduction of the host's activity and movement, restricting mussel dispersal (Horký et al, 2014). Similar to our study, Terui et al (2014) found an overall upstream bias in movements of Masu Salmon (Oncorhynchus masou masou), the host of the Japanese freshwater pearl mussel (Margaritifera laevis), recapturing *70% of hosts near original capture locations.…”
Section: Discussionsupporting
confidence: 78%
“…Based on previous studies investigating the sinking and drift rates of juvenile mussels (Schwalb et al, 2010;Irmscher, 2014), we estimated that juveniles drift approximately 50-250 cm during summer low flow conditions in the Little River, which is within the same range of upstream movement of host fish that we measured. Studies of mussel-host relationships have frequently investigated luring strategies and other aspects of glochidia-host interactions that enhance recruitment (e.g., Sietman et al, 2012); however, upstream dispersal is an additional advantage that mussels gain from the relationship with their host (Mansur & da Silva, 1999;Barnhart et al, 2008;Horký et al, 2014). Our study of host fishes at four sites in one season is a snapshot in time and space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glochidia can affect movement activity and local habitat selection of host fish through triggering immune responses (Horky et al, 2014). Although we could not compare dispersal patterns between infected and non-infected fish, incorporating this aspect into sampling design might provide an informative and fruitful avenue for research.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating P. nigrofasciata behavior and movement patterns during the M. walkeri parasitic larval stage is useful to characterize the mussel's dispersal and recruitment capabilities (Schwalb et al 2011, Horký et al 2014, Jones et al 2015. P. nigrofasciata have been shown to be 'long-term residents' that generally live in small areas of about 30 m with only a few fish documented to move up to 420 m (Freeman 1995).…”
Section: Early Life History Investigationsmentioning
confidence: 99%